HUBUNGAN PENAMPILAN, RASA DAN KERAMAHAN PENYAJIAN TERHADAP SISA MAKANAN PADA PASIEN RAWAT INAP RSUD AROSUKA SOLOK - Nurhamidah, Nurhamidah; Yensasnidar, Yensasnidar; Manora, Elsa (Sainstek : Jurnal Sains dan Teknologi, 2019)
Nutrition services in the hospital are services provided and adapted to the circumstances patient based on clinical states, nutritional and the body?s metabolism status. The success of a food establishment is o often associated with the remaining food consumed by the patient. This study aims to determine the relationship of the quality, hospitality and the accuracy of serving food to the rest of soft foods in hospitalized patients at the Hospital Arosuka Solok. The desain study is a cross sectional. Samples were taken by using accidental sampling, with a total samples of 50 people (Adults around 17 and above of age). The result of univariate shows that patient leave the soft foods served. Statistical test results show the appearance of food, taste, hospitality presenter officials relationship the remaining soft food patients. While the result of statistical of the timeliness of presentation does not significant relationship (p=0.05). It is hopped installation of officers Arosuka Hospital nutrition increase the quality in the taste of food by providing training and comparative study so that the food processing personnel can produce high quality food. The nutritionist of the hospital should monitor food taste before serving it and can tace care of serving method which includes food serving color, shape and place so that, the food appearance will be attractive.